1992
DOI: 10.1111/j.1440-1827.1992.tb03252.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pulmonary Adenocarcinoma with Sarcomatous Elements Initially Manifested as a Submucosal Tumor of the Stomach

Abstract: A case of pulmonary adenocarcinoma, which was initially manifested as a gastric submucosal tumor, is presented. Endoscopy showed a submucosal tumor in the fundic region in a 79‐year‐old Japanese woman. Initial biopsy specimens of the stomach revealed atypical spindle cell proliferation, suggesting primary leiomyosarcoma of the stomach. However, biopsy specimens obtained one year later were diagnosed as malignant lymphoma or malignant histiocytosis of the stomach. Autopsy revealed a large necrotic lesion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Therefore, whenever a submucosal tumor composed of carcinomatous and sarcomatous components is found in the gastrointestinal tract, the lungs should be examined as a possible primary site. 8 In summary, in this study, we found that PC of the lung has distinctive clinicopathologic features and a poorer outcome than other NSCLCs. Massive coagulation necrosis was identified as a histologic prognostic factor for a poorer outcome of PC of the lung.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, whenever a submucosal tumor composed of carcinomatous and sarcomatous components is found in the gastrointestinal tract, the lungs should be examined as a possible primary site. 8 In summary, in this study, we found that PC of the lung has distinctive clinicopathologic features and a poorer outcome than other NSCLCs. Massive coagulation necrosis was identified as a histologic prognostic factor for a poorer outcome of PC of the lung.…”
Section: Discussionmentioning
confidence: 48%
“…Fukuda et al reported a case of pulmonary adenocarcinoma with sarcomatous elements initially manifested as a submucosal tumour of the stomach. However, autopsy revealed spindle cell variants of pulmonary adenocarcinoma [25]. An immunohistochemical study and the presence of a transitional zone are important for the diagnosis of primary or metastatic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Spindle cell variants of pulmonary adenocarcinoma in metastatic lesions have been reported. These reports concluded that the metastasis exclusively composed of spindle cells was misdiagnosed as leiomyosarcoma (2,3). Small intestinal occlusion by metastatic tumors is treated conservatively (4).…”
Section: Introductionmentioning
confidence: 99%